l-cysteine protected copper nanoparticles as colorimetric sensor for mercuric ions - Soomro, Razium A.; Nafady, Ayman; Sirajuddin; Memon, Najma; Sherazi, Tufail H.; Kalwar, Nazar H. (Talanta (Oxford), 2014)
This report demonstrates a novel, simple and efficient protocol for the synthesis of copper nanoparticles in aqueous solution using l-cysteine as capping or protecting agent. UV–visible (UV–vis) spectroscopy was employed to monitor the LSPR band of l-cysteine functionalized copper nanoparticles (Cyst-Cu NPs) based on optimizing various reaction parameters. Fourier Transform Infrared (FTIR) spectroscopy provided information about the surface interaction between l-cysteine and Cu NPs. Transmission Electron Microscopy (TEM) confirmed the formation of fine spherical, uniformly distributed Cyst-Cu NPs with average size of 34±2.1nm. X-ray diffractometry (XRD) illustrated the formation of pure metallic phase crystalline Cyst-Cu NPs. As prepared Cyst-Cu NPs were tested as colorimetric sensor for determining mercuric (Hg2+) ions in an aqueous system. Cyst-Cu NPs demonstrated very sensitive and selective colorimetric detection of Hg2+ ions in the range of 0.5×10−6–3.5×10−6molL−1 based on decrease in LSPR intensity as monitored by a UV–vis spectrophotometer. The developed sensor is simple, economic compared to those based on precious metal nanoparticles and sensitive to detect Hg2+ ions with detection limit down to 4.3×10−8molL−1. The sensor developed in this work has a high potential for rapid and on-site detection of Hg2+ ions. The sensor was successfully applied for assessment of Hg2+ ions in real water samples collected from various locations of the Sindh River. [Display omitted] •l-cysteine protected copper nanoparticles were synthesized in aqueous medium.•l-cyst Cu NPs were used as LSPR based calorimetric sensor for Hg2+ determination.•This newly developed LSPR nanosensor is simple, and highly cost effective.•Developed sensor can serve as a suitable alternative to those based on precious metals.